2011
DOI: 10.2478/s13531-011-0029-2
|View full text |Cite
|
Sign up to set email alerts
|

Simulating pile load-settlement behavior from CPT data using intelligent computing

Abstract: Analysis of pile load-settlement behavior is a complex problem due to the participation of many factors involved. This paper presents a new procedure based on artificial neural networks (ANNs) for simulating the load-settlement behavior of pile foundations embedded in sand and mixed soils (subjected to axial loads). Three ANN models have been developed, a model for bored piles and two other models for driven piles (a model for each of concrete and steel piles). The data used for development of the ANN models i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Alkroosh and Nikraz used a gene-expression-programming (GEP) model to investigate the correlation between pile axial capacity and data obtained in cone penetration tests. Simulations obtained a maximal coefficient R value of 0.96 between the pile axial capacity predicted by the GEP model and the actual pile capacity (Alkroosh and Nikraz 2011).…”
Section: Artificial Intelligence In Geotechnical Engineeringmentioning
confidence: 92%
See 2 more Smart Citations
“…Alkroosh and Nikraz used a gene-expression-programming (GEP) model to investigate the correlation between pile axial capacity and data obtained in cone penetration tests. Simulations obtained a maximal coefficient R value of 0.96 between the pile axial capacity predicted by the GEP model and the actual pile capacity (Alkroosh and Nikraz 2011).…”
Section: Artificial Intelligence In Geotechnical Engineeringmentioning
confidence: 92%
“…Alkroosh and Nikraz simulated the subsidence of pile foundations under loading in cone penetration tests (Alkroosh and Nikraz 2011). Experimental applications of ANN for predicting the axial settlement of pile foundations embedded in sand showed that the models accurately predicted the nonlinear behaviors of soil under loading.…”
Section: Artificial Intelligence In Geotechnical Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Pile foundations are structural elements constructed underneath superstructures, frequently utilised as load carrying systems and soil settlement controls at sites with poor soil bearing capacity at sub-soil layers (Nazir and Nasr, 2013;Tomlinson and Woodward, 2014;Tschuchnigg and Schweiger, 2015). Pile bearing capacity and settlement are the most significant factors that influence pile foundation design procedures (Alkroosh and Nikraz, 2011;Alizadeh et al, 2012;Das, 2015;Nejad and Jaksa, 2017), making this a core feature of research in the field of geotechnical engineering. Accordingly, several procedures concerning pile bearing capacity, are available in the open literature, ranging from the application of complicated nonlinear numerical procedures to empirical relationships (Nasr, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 1,000 data sets, obtained from the literature, were used for model development. Alkroosh and Nikraz (2011) developed ANN models for simulating the load-settlement behaviour of pile foundations embedded in sand or mixed soils, subjected to vertical loads.…”
Section: Introductionmentioning
confidence: 99%